Evaluasi Usability Aplikasi MyASN Menggunakan Metode System Usability Scale (SUS) - Aqfi Nur Firdaus; Nia Rahma Faudila Harun; Zulfaidil (Jurnal Teknologi informasi dan Ilmu Komputer, 2026)
The rapid digital transformation in the public sector necessitates the development of service applications that are not only functionally robust but also highly usable. MyASN, as a digital personnel service platform for Indonesian civil servants (Aparatur Sipil Negara/ASN), is designed to facilitate access to employment-related information and administrative services. However, its implementation has revealed several usability issues, including login difficulties, slow system responsiveness, and feature instability, which negatively affect the overall user experience. This study aims to evaluate the usability level of the MyASN application using the System Usability Scale (SUS) method. Data were collected through the distribution of SUS questionnaires to application users. The results indicate an average SUS score of 54.08, which falls below the standard benchmark, placing the application in the Not Acceptable – Marginal category, with an adjective rating of Poor–OK and a grade of D. Furthermore, the Net Promoter Score (NPS) falls into the Detractor category, indicating low user satisfaction and a limited likelihood of recommendation. These findings suggest that the MyASN application exhibits significant shortcomings in terms of interface design, navigation, feature consistency, and system performance. Therefore, improvements are required, particularly in simplifying the user interface, enhancing system stability, and optimizing overall performance to improve user experience and the quality of digital personnel services.